Religious Polemics and the Participation of Yorùbá Muslims in Nigeria’s Democratic Dispensation: An Overview of Al-Asrau’s Perspective - Arikewuyo , Nafiu Ahmed; Abubakar, Sa’adallah Abdullahi (Kashere Journal of Politics and International Relations, 2025)
Politics is a set of happenings that are linked with the governance of the people. The year 1999 marked a watershed in the political history of Nigeria with the transition from military to civilian rule and since then, the country’s political arena has become vibrant with several significant political issues. Islam, according to the Muslims, is a system that pervades every human sector including politics. Democracy being a Western system has constituted bone of contention among Muslims across the globe, including Yorubaland of Nigeria. It is within that context that a renowned Muslim jurist in the region, Dr. Sirajudeen bin Bilal al-Asrau wrote his seminal work. The present attempt aims to highlight Al-Asrau’s submission to the political cum religious polemics among contemporary Muslims in Yorubaland. The study adopts an analytical method of research. Some of the findings of the study include the majority of Muslim jurists across the globe have validated the participation of Muslims in the democratic processes, based on either the ground of necessity or a firm belief that democracy is not totally alien to Islam. This is also the position promoted by al-Asrau in his work. The study recommends more political awareness for the Muslims in Yorubaland as a major means to actualize right to religious freedom and prevent religious harassment and persecution.